Safety and efficacy of pralsetinib in RET fusion-positive non-small-cell lung cancer including as first-line therapy: update from the ARROW trial - Griesinger, Frank; Curigliano, G.; Thomas, Michael; Subbiah, V.; Baik, C. S.; Tan, D. S. W.; Lee, D. H.; Misch, D.; Garralda, E.; Kim, D. -W.; van der Wekken, A. J.; Gainor, J. F.; et al. (Annals of oncology, 2022)
Background - RET fusions are present in 1%-2% of non-small-cell lung cancer (NSCLC). Pralsetinib, a highly potent, oral, central nervous system-penetrant, selective RET inhibitor, previously demonstrated clinical activity in patients with RET fusion-positive NSCLC in the phase I/II ARROW study, including among treatment-naive patients. We report an updated analysis from the ARROW study. - Patients and methods - ARROW is a multi-cohort, open-label, phase I/II study. Eligible patients were ≥18 years of age with locally advanced or metastatic solid tumours and an Eastern Cooperative Oncology Group performance status of 0-2 (later 0-1). Patients initiated pralsetinib at the recommended phase II dose of 400 mg once daily until disease progression, intolerance, consent withdrawal, or investigator’s decision. The co-primary endpoints (phase II) were overall response rate (ORR) by blinded independent central review and safety. - Results - Between 17 March 2017 and 6 November 2020 (data cut-off), 281 patients with RET fusion-positive NSCLC were enrolled. The ORR was 72% [54/75; 95% confidence interval (CI) 60% to 82%] for treatment-naive patients and 59% (80/136; 95% CI 50% to 67%) for patients with prior platinum-based chemotherapy (enrolment cut-off for efficacy analysis: 22 May 2020); median duration of response was not reached for treatment-naive patients and 22.3 months for prior platinum-based chemotherapy patients. Tumour shrinkage was observed in all treatment-naive patients and in 97% of patients with prior platinum-based chemotherapy; median progression-free survival was 13.0 and 16.5 months, respectively. In patients with measurable intracranial metastases, the intracranial response rate was 70% (7/10; 95% CI 35% to 93%); all had received prior systemic treatment. In treatment-naive patients with RET fusion-positive NSCLC who initiated pralsetinib by the data cut-off (n = 116), the most common grade 3-4 treatment-related adverse events (TRAEs) were neutropenia (18%), hypertension (10%), increased blood creatine phosphokinase (9%), and lymphopenia (9%). Overall, 7% (20/281) discontinued due to TRAEs. - Conclusions - Pralsetinib treatment produced robust efficacy and was generally well tolerated in treatment-naive patients with advanced RET fusion-positive NSCLC. Results from the confirmatory phase III AcceleRET Lung study (NCT04222972) of pralsetinib versus standard of care in the first-line setting are pending.